2023
DOI: 10.1007/s10531-023-02567-1
|View full text |Cite
|
Sign up to set email alerts
|

Rock climbing affects cliff-plant communities by reducing species diversity and altering species coexistence patterns

Abstract: Cliffs are unique ecosystems with an outstanding but relatively unknown plant diversity, harboring rare, endemic and threatened species, but also rock-specialist or generalist species that can become locally common and dominant on cliffs. The rising popularity of climbing represents an increasing threat to cliff biota, affecting community composition and potentially diminishing diversity and species associations. We used a novel sampling design of closely-paired climbed versus unclimbed points along the cliff-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Furthermore, our study provides a new interpretation of results from previous studies on this topic. Our findings on the effect of route opening within and in the areas close to the climbing routes suggest that the climbing effects previously found in other studies with closely-paired designs showed conservative results (e.g., Clark and Hessl, 2015;Tessler and Clark, 2016;Boggess et al, 2017;Reding, 2019;March-Salas et al 2018, 2023b. The climbing impact found in these studies should then be primarily attributed to the repeated climbers' ascents rather than to the opening of the climbing route, which is clearly the bottleneck of the detrimental process.…”
Section: The Origin and Extent Of Climbing Impactsupporting
confidence: 39%
See 2 more Smart Citations
“…Furthermore, our study provides a new interpretation of results from previous studies on this topic. Our findings on the effect of route opening within and in the areas close to the climbing routes suggest that the climbing effects previously found in other studies with closely-paired designs showed conservative results (e.g., Clark and Hessl, 2015;Tessler and Clark, 2016;Boggess et al, 2017;Reding, 2019;March-Salas et al 2018, 2023b. The climbing impact found in these studies should then be primarily attributed to the repeated climbers' ascents rather than to the opening of the climbing route, which is clearly the bottleneck of the detrimental process.…”
Section: The Origin and Extent Of Climbing Impactsupporting
confidence: 39%
“…To assess the strength and the origin of the climbing impact, we used a case-control design with a 3 m wide × 3 m high quadrat positioned at three zones of the climbing route (see March-Salas et al 2023b). The quadrat consisted of: a central plot of 1 m width and 3 m height representing the central area of the climbing route (so called 'within the climbing route'); two immediately adjacent surveyed plots of 0.5 m width and 3 m height, as this area could be potentially used by climbers during their ascent, and therefore would not be exempt from being disturbed; two plots 1 m far from the center of the climbing route of 0.5 m width and 3 m height on the left and right sides of the 3 m × 3 m quadrat that served as controls, representing areas not reached by climbers and outfitters (so called 'near the climbing route').…”
Section: Field Monitoring Methods and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation